Role of CEACAM1, ECM, and Mesenchymal Stem Cells in an Orthotopic Model of Human Breast Cancer - Sridhar Samineni; Carlotta Glackin; John E. Shively (International Journal of Breast Cancer)
Carcinoembryonic antigen-related cell adhesion molecule-1 (CEACAM1) is a morphogen in an in vitro model for lumen formation and plays a similar role in breast epithelial cells implanted in humanized mammary fat pads in NOD-SCID mice. Although extra cellular matrix alone is sufficient to stimulate lumen formation in CEACAM1 transfected MCF-7 cells grown in 3D culture, there is an additional requirement for stromal or mesenchymal cells (MSCs) for these cells to form xenografts with glandular structures in an orthotopic site. We demonstrate that optimal in vitro conditions include both Matrigel and MSCs and that the inclusion of collagen I inhibits xenograft differentiation. Additionally, there is no need to remove the nascent murine mammary gland. The previously observed difference in gland development between the long and short cytoplasmic domain isoforms of CEACAM1 is no longer observed in pregnant NOD/SCID mice suggesting that stimulation of the mammary fat pad by pregnancy critically affects xenograft differentiation.